1997
DOI: 10.1103/physreve.55.4909
|View full text |Cite
|
Sign up to set email alerts
|

Self-similarity and transport in the standard map

Abstract: Anomalous transpor is investigated for the Standard Map. A chain of exact self similar islands in the vicinity of the period 5 accelerator island is found for a particular value of the map parameter. The transport is found to be superdiffusive with an anomalous exponent related to the characteristic temporal and spatial scaling parameters of the island chain. The value of the transport exponent is compared to the theory. The escape time distribution and Poincare recurrence distribution are found t o have power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 25 publications
0
42
0
Order By: Relevance
“…In the first case that we have considered the main structure of the phase space is a self-similar hierarchy of chains of satellite islands. The anomalous diffusion in the presence of such structures has been previously observed and described in a series of papers [4][5][6][33][34][35][36] . It has been shown that the transport exponent is determined by two parameters which describe the selfsimilarity of the islands-around-islands structure.…”
Section: Numerical Investigationsmentioning
confidence: 87%
See 1 more Smart Citation
“…In the first case that we have considered the main structure of the phase space is a self-similar hierarchy of chains of satellite islands. The anomalous diffusion in the presence of such structures has been previously observed and described in a series of papers [4][5][6][33][34][35][36] . It has been shown that the transport exponent is determined by two parameters which describe the selfsimilarity of the islands-around-islands structure.…”
Section: Numerical Investigationsmentioning
confidence: 87%
“…Such unexpected behaviors have been observed for maps [1][2][3][4][5][6] as well as for incompressible two-dimensional fluid flows. [7][8][9] The main characteristic of an anomalous diffusion process is that the mean square displacement does not grow linearly in time…”
Section: Introductionmentioning
confidence: 92%
“…curve breaks and unbounded diffusion in action space takes place. Nevertheless even for K >> 1 some small stability islands survive in the classical phase space, correspondent to accelerator modes [23][24][25]. In fig.7 the classical phase space of the map (8) for K = 2.21 with the stability islands of accelerator modes is shown.…”
Section: Kicked Rotator Modelmentioning
confidence: 99%
“…3 and 4 supporting the powerlaw distributions P(s) and P(n) are already significant for understanding the anomalous large scale plasma behavior, the analysis may be much more effective if we can obtain an equation governing the distribution of density fluctuations. Here, we propose to use phenomenological fractional generalization of the Fokker-Planck-Kolmogorov ͑FFPK͒ equation, 13,14 which was successfully applied to some chaotic maps 15,28,29 as well as to the running sand-pile model. 16 For this goal, we introduce a distribution function F s (s,t) that describes only a singular part of the full distribution function…”
Section: Description Of the Fractional Kineticsmentioning
confidence: 99%